Dendroclimatological assessment of Polylepis rodolfo-vasquezii: A novel Polylepis species in the Peru highlands - Requena-Rojas E.J. (2020)
In spite of enormous diversity in tree species, dendrochronological records in the tropical Andes are very scarce. Therefore, it is necessary to increase the search for new tree species with high dendrochronological characteristics in the tropical Andes, including the humid Puna of Peru. We present the first tree-ring chronology from Polylepis rodolfo-vasquezii, a recently described tree species in the Central Andes of Peru between 4000 and 4400 m elevation. Fifty trees were sampled in the district of Comas, Peru. After establishing the anatomical characteristics that delimit the annual growth rings, we developed a ring-width chronology by applying conventional dendrochronological techniques. The chronology covers the period 1869–2015 (157 years) and is well replicated from 1920 to present (> 20 samples). The statistics used to evaluate the quality of the chronology indicate that the P. rodolfo-vasquezii has similar values of MS, RBAR and EPS to those shown by other Polylepis spp chronologies. To determine the main climatic factors controlling the growth of P. rodolfo-vasquezii, we compared our chronology with local and regional temperature and precipitation records. Growth season temperature (November to May) seems to be the main climatic factor modulating inter-annual variations in the growth of this species. The sensitivity to inter-annual temperature variations highlights the potential of P. rodolfo-vasquezii to provide climatically sensitive dendrochronological records in the Central Andes. To our knowledge, this is the first tree-ring record in South America displaying significant relationships with temperature over the tropical Atlantic Ocean. © 2020 Elsevier GmbH